IMPLEMENTASI CARA DISTRIBUSI OBAT YANG BAIK PADA PEDAGANG BESAR FARMASI DI YOGYAKARTA - Putra, Anthonius Ade Purnama; Hartini, Yustina Sri (Jurnal Farmasi Indonesia, 2012)
Government Regulation of The Republic of Indonesia number 51/ 2009 stated thatPharmacist must be the person that responsible for pharmaceutical wholesaler activity.Pharmaceutical wholesaler must implement Good Distribution Practices (GDP). There are79.045 types of registered pharmaceuticals that distributed by 2.821 pharmaceuticalwholesalers in 33 Indonesiaâ??s provinces. This research aimed to evaluate theimplementation of GDP on pharmaceutical wholesalers in Daerah Istimewa Yogyakarta(DIY) Province. This research conducted in July 2010 using questionnaire and interview to29 pharmaceutical wholesaler are willing to become respondents from 49 pharmaceuticalwholesaler listed in DIY. The products distributed by pharmaceutical wholesaler in DIYProvince which is the raw material of pharmaceuticals, vaccines, psychotropic, prescriptiondrugs, over the counter drugs, cosmetics, food, milk, and medical equipment. Theresponsible person in 83% pharmaceutical wholesaler is a woman, 38% chargepharmaceutical wholesaler 23-30 years old, pharmacist being the responsible person on31% pharmaceutical wholesaler, 52% had never been in charge GDP training. There are 3%pharmaceutical wholesaler which doesnâ??t have a Standard Operating Procedure, 21% donâ??thave the organizational structure, 59% didnâ??t have temperature control equipment, 34% donâ??thave humidity control equipment, 3% donâ??t carry out the documentation, and 10% didnâ??tconduct self inspections.Â ABSTRAKTerdapat 79.045 jenis sediaan farmasi yang berizin edar yang didistribusikan oleh 2.821PBF yang tersebar di 33 provinsi di Indonesia. Penelitian ini mengevaluasi implementasiCDOB pada PBF di Provinsi Daerah Istimewa Yogyakarta (DIY). Survei dilakukan bulan Juli2010 menggunakan kuesioner dan interview kepada 29 PBF yang bersedia menjadiresponden dari 49 PBF yang tercatat di Propinsi DIY. Hasil penelitian menunjukkan bahwaproduk yang disalurkan oleh PBF di Provinsi DIY yakni bahan baku farmasi, vaksin,psikotropik, obat keras, obat bebas, obat bebas terbatas, kosmetik, makanan, susu, danalat kesehatan. Sebanyak 83% PBF, penanggung jawabnya wanita, 38% penanggung jawabPBF berumur 23-30 tahun, 31% penanggung jawab PBF adalah apoteker, 52% penanggungjawab PBF belum pernah mengikuti pelatihan CDOB. Terdapat 3% PBF yang tidak memilikiStandar Operasional Prosedur, 21% tidak memiliki struktur organisasi, 59% tidak memilikialat pengontrol suhu, 34% tidak memiliki alat pengontrol kelembaban, 3% tidakmelaksanakan dokumentasi, dan 10% tidak melakukan inspeksi diri.